(untitled) (Research, Society and Development, 2021)
This work aims to study electrooculographic signals (EOG) from the acquisition, including windowing, and application of digital filters for processing and analysis. EOG is a signal that measures and records the resting potential of the eye retina. Herein, we develop an algorithm to detect eyeball movement signals relative to electrodes fix to face. The bioelectric signals were collected from 40 healthy adult volunteers. The applied methodology follows the international standards and guidelines for data acquisition of ECG signals and with the agreement of the institutional Research Ethics Committee. Two digital filters Savitzky-Golay (SG) and Median Filter (FM), were compared. As a result, were development and registration of software for windowing signals and the comparison between digital filters, with Savitzky-Golay being the most suitable for using with EOG.